Optimizing the Performance of State Civil Servants in the Secretariat of the Gorontalo Province Education and Training Agency - Yusuf Kasim; Ellys Rachma; Tety Thalib (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to describe the optimization of the performance of the State Civil Apparatus in the Secretariat of the Gorontalo Provincial Education and Training Agency. This study uses a qualitative approach. Data collection techniques using observation techniques, interview techniques, and documentation studies. Data analysis using qualitative analysis is inductive. The results of the research show that ASN's Work Results, Competence, Initiatives, Discipline have shown good results. However, ASN still need the opportunity to take part in training so they can improve their competence. In addition, there are several ASNs who develop new ideas in solving problems in carrying out their duties. In terms of discipline, it shows that there are still ASN personnel who have a low level of discipline. Discipline plays a very important role in the implementation of employee work.